RFID Device Development With MQTT To Prevent Attendance Cheating on Narotama University Student - aldi ruliansyah (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2021)
Presence is one of the important things, both in the school environment and in the work environment. Through the presence of an officer or staff can find out the presence of someone both in the work environment and in the school environment. The application of IoT in the school environment, especially at the university has been widely applied, but there are some problems such as cheating when making attendance to get the value of attendance in the classroom, therefore the application of this technology must be developed to prevent students from cheating when making attendance. The use of the Raspberry, Rdm6300 device and also the use of MQTT broker, the expected results in this study, the device that has been developed can prevent students from cheating while doing attendance and also makes students more disciplined, the use of MQTT broker on this device is so that each device in the Classes will only take attendance pages according to classrooms, and classrooms will change every 10 minutes when staff change courses and class hours Keywords : MQTT, RFID, Rasberry